A pyrrocidine derivative produced by fungus Neonectria ramulariae In-2 isolated from a Beetle Holotrichia picea. (August 2018) - Shiono, Yoshihito; Furukawa, Mariko; Koseki, Takuya; Kwon, Eunsang; Kurniawan, Andreas Hendracipta; Sato, Satoru; Harneti, Desi; Maharani, Rani; Supratman, Unang; Uesugi, Shota; Kimura, Ken-ichi
Graphical abstract: Highlights: Cytotoxicity of metabolite produced by a fungal Nectria pseudotrichia In-2. Isolation of a new pyrrocidine derivative, 19- epi -pyrrocidine A The structure was elucidated on the basis of spectroscopy analyses. Abstract: A new pyrrocidine A derivative, 19- epi -pyrrocidine A (1 ) was isolated from the insect–derived fungus Neonectria ramulariae In-2, together with known pyrrocidine A (2 ). The structure of 1 was determined by extensive 1D- and 2D-NMR, and MS spectral analyses. The absolute configuration of 2 was confirmed for the first time by X-ray crystallography. Compound 1 exhibited cytotoxicity against human acute promyelocytic leukemia HL60 cells (IC50 2.05 μM). In addition, semi-synthetic compounds 19- O -methyl-pyrrocidine A (3 ), 19- O -acetyl-pyrrocidine A (4 ), and 1, 2-4, 5-17, 18-triepoxy-pyrrocidine A (5 ) were found to possess significant cytotoxicity, with IC50 values of 0.66 μM, 0.19 μM, and 2.00 μM, respectively.